2011
DOI: 10.1371/journal.pone.0017399
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Larval Nutrition on Reproductive Performance in a Food-Limited Adult Environment

Abstract: It is often assumed that larval food stress reduces lifetime fitness regardless of the conditions subsequently faced by adults. However, according to the environment-matching hypothesis, a plastic developmental response to poor nutrition results in an adult phenotype that is better adapted to restricted food conditions than one having developed in high food conditions. Such a strategy might evolve when current conditions are a reliable predictor of future conditions. To test this hypothesis, we assessed the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
108
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(112 citation statements)
references
References 45 publications
3
108
0
1
Order By: Relevance
“…In this context, the reproduction may here be understood as a more or less stressful state that an organism must face according to its own developmental history (e.g. [23,24], but see [13]). In this case, we hypothesize that an early episode of oxidative stress could programme the organism to better face increased oxidative stress linked to reproductive effort.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, the reproduction may here be understood as a more or less stressful state that an organism must face according to its own developmental history (e.g. [23,24], but see [13]). In this case, we hypothesize that an early episode of oxidative stress could programme the organism to better face increased oxidative stress linked to reproductive effort.…”
Section: Introductionmentioning
confidence: 99%
“…Nutrition is a primary determinant of life span and reproductive capacity in all organisms, from yeast to humans [16][17][18], and its relationship to life history has been studied extensively. Developmental nutrition can have far-reaching effects on adult traits [19][20][21][22][23]. A wide array of insect literature has found that calorically poor food quality during development leads to increased development time, decreased adult weight [23][24][25][26], and reduced fecundity.…”
Section: Discussionmentioning
confidence: 99%
“…Developmental nutrition can have far-reaching effects on adult traits [19][20][21][22][23]. A wide array of insect literature has found that calorically poor food quality during development leads to increased development time, decreased adult weight [23][24][25][26], and reduced fecundity. However, the effect of nutrient AaILP3 are closer orthologs of dilp3 and dilp2, respectively (personal observation; sequence alignment).…”
Section: Discussionmentioning
confidence: 99%
“…However, what remains poorly understood is how diet and nutrition received at different life-stages (i.e. developmental versus adult life-stages) interact to influence individual adult performance (Møller et al, 2000;Monaghan, 2008;Dmitriew and Rowe, 2011;Butler and McGraw, 2012;Hopwood et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…To date, empirical tests of the Environmental Matching and Silver Spoon Hypotheses have primarily focused on investigating how the quantity of food received at different life-stages impacts fitness-determining traits (Dmitriew and Rowe, 2011;Hopwood et al, 2014). Interestingly, the majority of these studies have provided support for the Silver Spoon Hypothesis (see Ogilvy et al, 2012, Wong andKölliker, 2014), with relatively few studies providing support for the Environmental Matching Hypothesis (but see Butler and McGraw, 2012).…”
Section: Introductionmentioning
confidence: 99%